Mathematics Online Learning via WhatsApp: How Effective? - Al Ikhlas (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the effectiveness of online mathematics learning using the WhatsApp application on students’ learning outcomes at one junior high school in Kerinci, Jambi, Indonesia. This research is quantitative descriptive research. The sample of the research was eighth-grade students. The instrument used in this study was a questionnaire and test. The hypothesis was evaluated using the one-sample t-test. This study shows that online mathematics learning using the WhatsApp application during the Covid-19 was ineffective in improving the students’ learning outcomes.